Molecular Mechanisms of Interferon Resistance Mediated by NS3, NS4A and NS4B Genes of Hepatitis C Viruses in Chronic Hepatitis C Patients Treated with Peginterferon-α and Ribavirin - Pattranuch Chusri (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Several HCV genotypes circulating in Thailand has been reported, including HCV-1a, -1b, -3a, -3b and various subtypes of HCV-6. Standard regimen for the treatment of hepatitis C is based on the combination of pegylated inferferon-α (IFN-α) and ribavirin (RBV). The NS3 is a multifunctional protein, with a serine protease and helicase domains. The NS4A protein functions as a cofactor for the NS3 serine protease. The NS3-NS4A protease is responsible for cleavage of HCV polyprotein into several functional proteins while helicase is essential for HCV RNA replication and also plays a role in viral particle assembly. Several studies suggest that NS3-NS4A protease could be one of the factors that HCV uses to interfere with the host antiviral response. In addition, NS4B has been found to be responsible for the formation of the membranous web, which is the platform for viral replication. We hypothesized that amino acid variations in the NS3, NS4A and NS4B proteins may affect the functions of those proteins, and therefore interfere with the HCV replication. The present study aimed to assess the effects of HCV amino acid variations in NS3, NS4A and NS4B of HCV on the response to Peg-IFN and RBV treatment and also to investigate the inhibitory effects of NS3-NS4A proteins on the IFN-α signaling pathway by HCV-1a, -1b, -3a, -3b, and -6f. One hundred and thirty four patients infected with HCV-1a, -1b, -3a, -3b and -6f strains that showed different clinical outcomes, the responders and treatment failure group, at before treatment and at week 4 of treatment were evaluated.